Medication adherence among elderly patients with high blood pressure in Gweru, Zimbabwe - Elizabeth Wariva; James January; Julita Maradzika (AOSIS, 2014)
High blood pressure is a global health concern which is mainly managed by taking antihypertensive medications. Although medication is available to control high blood pressure, adhering to treatment is a major problem among hypertensive patients. The purpose of the study was to assess the predisposing, enabling and reinforcing factors to medication adherence among hypertensive patients in Gweru urban aged 40-70 years. A descriptive cross sectional study was used with a sample size of 110 conveniently sampled hypertensive patients. We used an interviewer administered questionnaire designed using phase 4 of the PRECEDE model. The modal age was 70 years and mean age was 58 years (SD=10.29). There were 61.8% females and 38.2% males. Variables associated with medication adherence were: age (P=0.0059), marital status (P=0.015), average monthly income (P=0.0002), support group (P=0.027) and knowledge (P=0.0058). Providing information to patients with high blood pressure and having a good patient-provider relationship improves medication adherence. There is need to focus on the predisposing, enabling and reinforcing factors of medication adherence since demographic and socio-economic factors may be more difficult to change.